Blood dendritic cells in systemic lupus erythematosus exhibit altered activation state and chemokine receptor function. Issue 7 (22nd October 2009) - Gerl, Velia; Lischka, Alexandra; Panne, Daniel; Großmann, Patrick; Berthold, Rita; Hoyer, Bimba Franziska; Biesen, Robert; Bruns, Anne; Alexander, Tobias; Jacobi, Annett; Dörner, Thomas; Burmester, Gerd-Rüdiger; et al.
Abstract : Background: Dendritic cells (DCs) have a pivotal role in the pathogenesis of systemic lupus erythematosus (SLE). Reduced numbers of blood DCs and the accumulation of DCs at inflammatory sites have been observed in SLE. One crucial feature of DCs is their ability to migrate. Objective: To analyse the maturation/activation state and the migratory capacity of different DC precursor subsets in SLE to further elucidate their role in autoimmunity. Methods: Plasmacytoid DCs (pDCs), myeloid DCs (mDCs) and monocytes from patients with SLE, healthy volunteers and healthy volunteers immunised with tetanus/diphtheria were examined by flow cytometry for expression of subset-specific antigens (BDCA-2, CD11c, CD14, HLA-DR), activation/maturation markers (CD83, CD86, CD40, BLyS) and chemokine receptors (CCR1, CCR5, CCR7, ChemR23). Additionally, migratory capacity to chemokine receptors was investigated in vitro using the chemokines RANTES, CCL19 and chemerin. Results: SLE monocytes and mDCs had higher CD86 and B-lymphocyte stimulatory factor (BLyS) expression levels. ChemR23 expression was lower in SLE pDCs and mDCs. Basal and CCL19-specific migration levels were higher in SLE pDCs. Altered DC function in SLE had no correlative changes in chemokine receptor expression, whereas immunisation-induced blood DC migration patterns in healthy donors were accompanied by changes in chemokine receptor expression. Conclusions: The phenotypic and migratory disturbances observed in SLE blood DCs could result in altered distribution of DCs in peripheral tissues, contributing to dysregulated immune responses and autoimmunity.